NURSES' EXPERIENCE IN CARRYING OUT NURSING CARE DOCUMENTATION USING ELECTRONIC MEDICAL RECORD (EMR) - Ginting, Dewi Susanna; Dewi, Wan Nisfha; Lestari, Widya; Bayhakki, Bayhakki; Erika, Erika (Jurnal Keperawatan, 2025)
The development of information and communication technology has led to significant changes in the provision of nursing care. This study examines nurses' experiences with using Electronic Medical Records (EMRs) for nursing care documentation. This study aims to explore the experiences of nurses using EMR in documenting nursing care. This qualitative study uses a phenomenological approach involving 10 nurses, including the head of the room, team leader, and implementing nurses. Participants were selected using purposive sampling techniques, with the following criteria: nurses who perform nursing care documentation using an Electronic Medical Record (EMR), nurses working in inpatient, outpatient, emergency (IGD), and intensive care units, nurses with a work experience of at least 2 years, and nurses who are willing to participate. The study was conducted at a private hospital in Pekanbaru. Data were collected through interviews and analysed using thematic analysis, employing the Colaizzi method. Result: The analysis revealed three themes: the benefits of Electronic Medical Records (EMR) in nursing services, supporting factors for the implementation of EMR, and inhibiting factors for the implementation of EMR. Based on the study results, it can be concluded that nurses feel the effectiveness and efficiency of EMR in documenting. However, during its implementation, there are still obstacles that require attention from hospital management. Thus, providing health services becomes optimal and efficient for patients and health workers.